Association Between Serum Uric Acid and Essential Hypertension In Bangladeshi Adults Attending the Outpatient Department of A Tertiary Medical College Hospital - Das, Sumon; Tasnim, Nayeema; Mohajan, Shimu; Dutta, Shantanu; Hasina, Hafsa; Barua, Maghna (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Among the many confounding factors linked to essential Hypertension (HTN) high Serum Uric Acid (SUA) is a promising biomarker. The study's objective was to determine how SUA levels and essential hypertension related in a major academic Hospital at Chattogram, Bangladesh. Materials and methods: This cross-sectional comparative study included 42 newly diagnosed hypertensive patients (Aged 18–65 years) as cases from Chittagong Medical College Hospital and 42 normotensive controls were matched in terms of age and gender. Results: The mean SUA level was 6.5±0.9 mg/dl (Range: 4.7-9.0) and 5.6±0.9 mg/dl (Range: 3.8-7.5) in the case and control group, respectively (p<0.001). The proportion of participants with Hyperuricemia was higher in the case group (17/42, 40.5%) than the control group (4/42, 9.5%) and the difference was significant statistically (p=0.001, Chi-square test). Conclusion: The number of participants with hyperuricemia and the mean serum uric acid levels were found to be considerably greater in cases than in controls. JCMCTA 2025 ; 36 (1) : 25-31